An Inverse Problem of Determining Coefficients in a One-Dimensional Radiative Transport Equation (Advances in Applied Mathematics and Mechanics, 2014)
We consider an inverse problem of determining unknown coefficients for aone-dimensional analogue of radiative transport equation.We show that some combination of the unknown coefficients can be uniquely determinedby giving pulse-like inputs at the boundary and observing the corresponding outputs.Our result can be applied for determination of absorption and scattering properties of anoptically turbid medium if the radiative transport equation is appropriate for describingthe propagation of light in the medium.